WHO IS THE AUDIENCE, EMPEROR? TARGETING AUDIENCES ON LATE ROMAN AND EARLY BYZANTINE COINS - Jehan HILLEN (Journal of Ancient History and Archaeology)
This article suggests that audience targeting occurred on late Roman and early Byzantine coins by differentiating imperial attributes on the obverse rather than images on the reverse. Although late Roman and early Byzantine coin types are substantially more standardized than previous Roman imperial issues there are still subtle differences to be found between the various metals and even denominations. By focusing on imperial attributes this article indicates the way in which targeted messages were sent by changing the representation and subsequent role of the emperor on the obverse. By analyzing the appearance of the so-called military and consular types, this article will provide two case studies of imperial representations that were struck on rare gold, and occasional silver, issues intended for a specific audience well into the Byzantine era. Additionally, these imperial representations were under specific circumstances also broadened to a larger audience using bronze coins.